Effects of thermal treatments on the characterisation and utilisation of red mud with sawdust additive. Issue 6 (June 2016) - Liu, Yanju; Naidu, Ravi; Ming, Hui; Dharmarajan, Rajarathnam; Du, Jianhua
Extremely large amounts of red mud (bauxite residue) are generated globally every year from alumina refining industries, which are being disposed of on engineered landfills. The objective of this study is to investigate the effects of thermal treatments on red mud for development of utilisation strategies. Thermal treatments of red mud samples and their characterisations were investigated under inert (N2 ) and oxidative (air) conditions with and without sawdust addition at 200–600°C. After calcination, the resulting samples were analysed using thermogravimetric–infrared spectroscopy (TG-IR) for functional group transformations, thermogravimetric analysis (TGA) for thermal loss profiles and X-ray diffraction (XRD) for mineral transformations. The characterisation results showed that in N2 environment, boehmite in red mud was transferred to transition alumina at around 400°C while losing water from structural components. The addition of sawdust for incubation and calcination of red mud in air increased the surface area, whereas that in nitrogen atmosphere lead to reduction of hematite to magnetite at around 500°C. The incorporated carbon materials played a major role in increasing the surface area especially for pore size less than 2.5 nm. This treated red mud with altered mineral composition and improved properties for binding contaminants can be used for environmental remediation and in the process of metal recovery such as iron.